Blue Economy Integration as a Management Strategy for Small-Scale Fisheries: Economic Valuation of Sustainable Coastal Aquaculture through Digital Market Platforms - Yuminarti, Umi (Smart International Management Journal, 2026)
This study investigates the strategic integration of blue economy principles within Indonesian small-scale fisheries (SSF) through the deployment of digital market platforms. This study examines the integration of blue economy principles. Utilizing a quantitative secondary data analysis combined with the Total Economic Value (TEV) framework and comparative statistical testing from the Ministry of Marine Affairs and Fisheries (KKP) and the Central Bureau of Statistics (BPS) for the 2020-2025 period, the study evaluates production metrics across three primary geographic clusters. The findings demonstrate that IoT-integrated management significantly optimizes operational efficiency, evidenced by a 22.09% reduction in the Feed Conversion Ratio (FCR) and a substantial elevation of the Fishers' Exchange Rate (NTPi) via direct market linkages. Furthermore, digital traceability was found to command a 15-20% price premium in international markets, effectively internalizing sustainability into financial assets. The research concludes that while digitalization serves as a powerful catalyst for coastal prosperity and resource resilience, its success remains contingent upon closing the digital infrastructure gap. These results offer a data-driven framework for policymakers to harmonize technological acceleration with environmental stewardship in the maritime sector.